Uporabnost in učinkovitost kanoničnega genetskega algoritma - Žumer, Gaja (Matrika, 2019)
Genetic algorithm is a stochastic optimisation method for solving difficult optimisation problems. This article first discusses its implementation, followed by examples indicating the inconveniences which may appear when dealing with putting genetic algorithm into practice. When searching for the best solution, genetic algorithm inspects areas with the higher probability of containing a globally optimal solution. Schema theorem tries to explain the mechanics behind genetic algorithm, but it cannot be used for the analysis of its convergence properties. For this purpose, finite homogeneous Markov chains need to be applied. The article comments on convergence of canonical genetic algorithm and two of its versions.
Keywords: canonical genetic algorithm; kanonični genetski algoritem; matematika; mathematics